Experimental and statistical analysis of low velocity impact response of filament wound composite pipes - Gemi, Lokman; Kayrici, Mehmet; Uludağ, Muhammet; Gemi, Dilek Soylu; Sahin, Omer Sinan (Elsevier Sci Ltd, 2018)
Nowadays, filament wound composite pipes (GRP) are used as a structural element in many applications such as natural gas and oil transmission lines, and portable bridge constructions for military purposes. GRP pipes can expose to impact loading from various causes. This loading can cause an invisible level of damage. Thus, the detection and evaluation of such damages are of great importance. In this study, the low velocity impact response of (+/- 55 degrees)(3) filament wound E-glass/epoxy composite pipes has been studied. The pipes have been subjected to drop weight impact loading with various impact energies. The force-time and force-displacement relations have been examined. The impact damage formation was also evaluated. It is concluded that the damage development in the pipes is controlled by displacement trough radial direction. The obtained results were evaluated statistically by means of Weibull approach. Microscopy analysis of impacted region revealed that debonding, radial cracks, transfer cracks and delamination damage modes are the main observed damage modes.
Keywords: Damage formation; Filament wound pipes; Lognormal distribution; Low velocity impact; SEM; Weibull analysis